TOPONIM WILAYAH KOTA PEKANBARU: ETNISITAS, PENGGUNAAN BAHASA, DAN CAMPUR KODE - Budiono, Satwiko; Wijayatiningsih, Yenni Febtaria; Yance, Imelda (UI Scholars Hub, 2023)
Urban areas have developed rapidly in terms of demography and culture. This is because urban areas attract people who are searching for higher income and a better life than those in rural areas. Demographical and cultural development in urban areas often affects local culture. One example can be found in Pekanbaru City, Riau Province, Indonesia. The Riau Malays, the city’s native ethnic group, no longer dominates the city’s demographical landscape. In fact, the Minangkabaus as a migrant ethnic group actually dominate Pekanbaru City. However, there is still a limited body of documentation of and research on the language and culture in Pekanbaru City. Therefore, this study was conducted to investigate the toponyms of various areas in Pekanbaru City. This research is also intended to reveal the meaning of less popular local toponyms to provide valuable information for the general public. This research used the qualitative method with the toponymic approach. Data consist of all sub-district names in Pekanbaru City. Analysis was conducted to classify those names based on their basic toponymy, focusing on their lexico-semantic aspects. The meaning of those toponyms was obtained from interviews with selected respondents. In addition, this study also connects toponymy with various sociolinguistic aspects, especially ethnicity, language use, and code-mixing. Results show that most local toponyms in Pekanbaru City refer to certain geographical conditions, trees, hopes, and rivers. Furthermore, most local toponyms contain roots which originated from Indonesian, Riau Malay, and Javanese languages. In terms of ethnicity, Pekanbaru City is dominated by the Minangkabaus, Riau Malays, and Javanese. The dominant languages in Pekanbaru City are Indonesian, Minang, and Riau Malay. Code-mixing in local toponyms mostly occur between Indonesian and Javanese. However, not all sub-district names have identifiable toponymic meaning, so further research is needed to complement the existing results.